Food and Fitness: Myths and Truths - Linda B. Bobroff; Amy Mullins (EDIS, 2015)
Do you know how much water you should drink before exercise? Does loading up on carbs before a strenuous cardio workout improve performance? This revised 6-page fact sheet debunks some common myths about nutrition and fitness and offers other helpful advice for those who wish to stay active and eat a healthy diet. Written by Linda B. Bobroff and Amy Mullins, and published by the UF Department of Family, Youth and Community Sciences, June 2015.